2004
DOI: 10.1021/jp036607u
|View full text |Cite
|
Sign up to set email alerts
|

Anionic Species (FH)xF- in Room-Temperature Molten Fluorides (CH3)4NF·mHF

Abstract: Ionic and nonionic species in (CH3)4NF·mHF melts (m = 3.0−5.0) were investigated by 1H NMR, IR spectroscopy, Raman spectroscopy, and high-energy X-ray diffraction measurements. Three types of anions, (FH)F-, (FH)2F-, and (FH)3F-, were identified in these melts. The (FH)2F- anion was thermodynamically the most stable of the complex anions in the (CH3)4NF·mHF (3.0 ≤ m ≤ 5.0), and its concentration was the highest. (FH) x F- anions with x = 4 and 5 were not present at room temperature though the presence of (FH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 34 publications
5
47
1
1
Order By: Relevance
“…Structural characteristics of EMImFHF at both the liquid and solid states and RMIm(FH) 2.3 F in the liquid state were studied using X-ray diffraction techniques [23][24][25]. Some spectroscopic data are also available for TMA(FH) n F (TMA = tetramethylammonium, n = 3.0-5.0) salts that show some HF dissociation pressures at ambient temperatures [26]. Cs(FH) 2.3 F is also a potential electrolyte for electrochemical energy conversion devices like other fluorohydrogenate salts.…”
Section: Introductionmentioning
confidence: 99%
“…Structural characteristics of EMImFHF at both the liquid and solid states and RMIm(FH) 2.3 F in the liquid state were studied using X-ray diffraction techniques [23][24][25]. Some spectroscopic data are also available for TMA(FH) n F (TMA = tetramethylammonium, n = 3.0-5.0) salts that show some HF dissociation pressures at ambient temperatures [26]. Cs(FH) 2.3 F is also a potential electrolyte for electrochemical energy conversion devices like other fluorohydrogenate salts.…”
Section: Introductionmentioning
confidence: 99%
“…In a solution such as DME, Et 4 NFÁ4HF may dissociate to Et 4 N + , F(HF)n À (n = 1-3), and HF [30][31][32][33]. Moreover, it was also found that DME was oxidized simultaneously during the electrolysis of substrates, which can suppress overoxidation of both the substrates and products, particularly at a later stage of the electrolysis [27].…”
Section: Solvent Effect On the Efficiency Of Selective Anodic Fluorinmentioning
confidence: 92%
“…The (FH) n F − anions are regarded as an ion where F − is bound to one or more HF molecules. The H−F bond in (FH) n F − is known as "strong hydrogen bond" [9] and has been a target of theoretical and computational studies [10][11][12][13] as well as X-ray diffractional and vibrational spectroscopic studies. The smallest fluorohydrogenate ion is FHF − with D ∞h symmetry which is determined in a number of crystal structures ( Figure 5.2 (a)) [5,[14][15][16][17][18][19][20][21][22].…”
Section: Structural Properties Of Fluorohydrogenate Anionsmentioning
confidence: 99%